DA HEREDITARIEDADE BIOLÓGICA À HEREDITARIEDADE SOCIAL: o pensamento educacional do médico Achilles Lisboa (1920/1930). - LIMA, Benedita Rosângela Leite (2016)
This work aims to analyze the performance of the medical Achilles Lisbon in the field of education through its publications, especially through the work On the best way of promotion of primary education in Brazil. We try to understand the construction of his thought permeating by their readings and their social and political construct. Therefore we draw a path for the study of the concepts of bias hygienism, sanitirarismo notions of civilization. We also seek to rebuild through their own written his life story and social trajectory and from these to understand the formation of his thought and the process that gave the formulation of his educational theory - social heredity. Concept that will introduce, develop and minuciar throughout this work.